Fetal subjects and maternal objects: Reproductive technology and the new fetal/maternal relation. - Squier, Susan (Journal of Medicine & Philosophy)
Examines three psychological tendencies nurtured in the practices of reproductive technology. Increase in the use of visualization technologies; Contrast between the pre-19th century and Western view about pregnancy; Revision of the notion about maternal-fetal relation; Historical and contemporary representations of pregnancy.